FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO INFEKSI SALURAN KEMIH PADA PASIEN DIABETES MELLITUS: A Literature Review - Purwandari Nurfaizah (2020)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia because the body lacks insulin which has the function to metabolize blood sugar. Diabetes mellitus is often considered as a risk factor for urinary tract infection. Urinary tract infection is the most common infectious disease that attacks urinary tract. This study aims to examine the existing researches to determine the best evidence related to the factors that influence the risk of urinary tract infection in patients with diabetes mellitus. This study was conducted with qualitative research method by doing several literature reviews in which literature searches were performed using electronic databases such as PubMed and Google Scholar while taking into account the inclusion criteria which are full-text accessible journals that discuss the risk factors for urinary tract infections in diabetes mellitus patients with a time limit of the release of the last 10 years. Based on the literature review of a total of 7 journals, there are 11 variables act as factors that influence the risk of urinary tract infection in patients with diabetes mellitus which can be grouped into 2 risk factors that are risk factors according to respondent characteristics and risk factors according to various diabetes conditions. The age, gender, and diabetes medication adherence risk factors are found to be the most dominant risk factors affecting the occurrence of urinary tract infection in diabetes patients.